1978
DOI: 10.1093/ije/7.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance and Blood Pressure in Two Population Samples: Their Relation to Diabetes Mellitus and Hypertension

Abstract: The relationship between blood pressure and the blood sugar concentration measured two hours after a 50 g oral glucose load has been examined in two population surveys-the Whitehall and Bedford Surveys. In the Whitehall Survey, which was conducted in men above the age of 40, there was a positive, significant correlation between blood sugar and blood pressure (systolic and diastolic) which was independent of common associations with age, body mass index (BMI) and heart rate. In the Bedford Survey, systolic bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(56 citation statements)
references
References 0 publications
3
51
2
Order By: Relevance
“…This absence of systematically different systolic (and diastolic) pressures in diabetic compared with non-diabetic subjects was also noted in the Whitehall Study when pressures in diabetic patients (men 40-64 years, mean systolic 137 mmHg) were measured in ignorance of their diagnosis and at the same time as a group of approximately 18 000 non-diabetic individuals (mean systolic 136 mmHg) [24]. There is inconsistency Cigarette smoking habits also show major variations between centres.…”
Section: Vascular 'Risk Factors'mentioning
confidence: 69%
“…This absence of systematically different systolic (and diastolic) pressures in diabetic compared with non-diabetic subjects was also noted in the Whitehall Study when pressures in diabetic patients (men 40-64 years, mean systolic 137 mmHg) were measured in ignorance of their diagnosis and at the same time as a group of approximately 18 000 non-diabetic individuals (mean systolic 136 mmHg) [24]. There is inconsistency Cigarette smoking habits also show major variations between centres.…”
Section: Vascular 'Risk Factors'mentioning
confidence: 69%
“…This relationship was present in both men and women after appropriate adjustment for age and weight. In the Whitehall study, patients with impaired glucose tolerance were found to have significant elevations of mean blood pressure, but the results were not significant for patients with overt diabetes (10). In the Framingham study, systolic hypertension was ~1.5 times more prevalent in diabetic than in nondiabetic patients, with the risk being higher in women than in men (11,12).…”
Section: Epidemiology and Prevalencementioning
confidence: 93%
“…They reported a 54% increase in the prevalence of hypertension (defined as a blood pressure >160/95 mmHg) in the diabetic patients. In the Bedford survey, patients with newly diagnosed diabetes as well as those with glucose intolerance were found to have a significantly higher prevalence of systolic hypertension compared with patients with normal glucose tolerance (10). This relationship was present in both men and women after appropriate adjustment for age and weight.…”
Section: Epidemiology and Prevalencementioning
confidence: 99%
“…Since systemic blood pressure is such an important factor for initiation and progression of diabetic nephropathy, we became interested in whether hyperglycaemia (acute, sub-acute or chronic), per se, induces an increase in systemic blood pressure. Evidence supporting this theory came from population-based studies of non-diabetic children 63 and diabetic and non-diabetic adults, 64 demonstrating a direct association between blood glucose level and arterial blood pressure. Some glycaemic intervention studies have shown an increase in systemic blood pressure after days/weeks of hyperglycaemia, 59,65 whereas this was not demonstrated by others.…”
Section: Experimental Evidence For Renal Ras Activationmentioning
confidence: 99%